Interpreting experimental fracture toughness results of quasi-brittle natural materials through multi-parameter approaches (Fracture and Structural Integrity, 2015)
Natural stones like marbles are often employed as façade panels to externally cover buildings. Thesenatural materials tend to exhibit a quasi-brittle nonlinear fracture behaviour which, conversely to concretecounterpart, has much less been studied in the literature. In the present paper, an experimental campaign on theso-called red Verona marble is carried out, and the results are discussed together with some previouslypublished results on the white Carrara marble. The analysis of the two marbles as a whole allows us to discusssize effect and to point out the need for additional parameters in order to describe their fracture behaviour. Thestudy focuses on a two-parameter model which accounts for a characteristic material length. A quantitativecorrelation between material microstructure features, obtained from thin sections technique, and thecharacteristic material length is proposed.
Keywords: Fracture process zone